Stock Return Prediction In Emerging Markets Using Machine Learning - Rizny, Mohamed Shezan (2023)
A Master of Science thesis in Engineering Systems Management by Mohamed Shezan Rizny entitled, “Stock Return Prediction in Emerging Markets Using Machine Learning”, submitted in November 2023. Thesis advisor is Dr. Zied Bahroun and thesis co-advisors are Dr. Hussam Alshraideh and Dr. Anis Samet. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).